EUROCHIP in action: A case study - Brito Ferrari, Antonio de (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes the experience of the Department of Electronics and Communications Engineering, Universidade de Aveiro, as a EUROCHIP Participating Institution (PI). The emphasis is on the analysis of the impact of EUROCHIP participation on' the curricula of the degree courses run by the department. In a short time the curricula has changed from a traditional one, with 110 VLSI contents, to one where VLSI design is becoming a very strong presence. What has been achieved so far through EUROCHIP is described as well as the plans for the near future.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka